Becoming Entrepreneurs After Graduating College - Effiyaldi; Yemima; Syafril; Wahyudi; Andi Makkulawu Panyiwi Kessi (Jurnal Entrepreneur dan Entrepreneurship, 2024)
This research aimed to analyze students' interest in becoming entrepreneurs after graduating from college. This research used a quantitative method. Data collection for this research was carried out by distributing an online survey to 146 respondents. This study results that students' interest in becoming entrepreneurs is quite high, but there are obstacles, namely not having initial capital for the business, not having business talent, not having a business network and being afraid of taking the risk of going bankrupt. This research is very important for universities in preparing reliable human resources for entrepreneurship and also as a guide for the government in creating jobs and the number of young entrepreneurs in Indonesia. Further research can be carried out at various different campuses.